EVALUATING THE EFFECTIVENESS OF CARBON CREDITS IN AGRICULTURE: CASE STUDIES FROM SOUTHEAST ASIA AND IMPLICATIONS FOR THE MEKONG DELTA, VIETNAM - Nguyen Bich Ha Vu (HUIT Journal of Science, 2025)
The agricultural sector in Southeast Asia is a significant contributor to global greenhouse gas emissions, necessitating the exploration of mitigation strategies such as carbon credits. This research evaluates the effectiveness of carbon credit mechanisms in agricultural practices, with a particular focus on rice farming across Thailand, Vietnam, and Indonesia. These countries were selected due to their prominence in Southeast Asian rice production and the presence of diverse carbon credit initiatives. Through a comparative case study analysis of existing carbon credit programs, this study examines their economic viability, technical feasibility concerning Measurement, Reporting, and Verification (MRV), and social equity impacts. The findings reveal both the potential and the challenges associated with these programs in incentivizing sustainable agricultural practices and reducing emissions. Based on the analysis, the report concludes with tailored recommendations for the application of carbon credits in the Mekong Delta region of Vietnam, considering its unique agricultural context and vulnerabilities to climate change.